The Integration of Artificial Intelligence for Generation Z in the Digital Era - Tria Lestari; Ikmah Wati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Artificial intelligence is a tangible proof of the rapid development of digitalization today. Artificial intelligence has a crucial influence on everyday life. Generation Z is a generation group that is very adept at using artificial intelligence. However, in the current digital era, many Generation Z still have not been able to utilize artificial intelligence wisely and responsibly. The low awareness and digital ethics possessed by Generation Z is a very serious problem and must be addressed immediately. The fading of critical thinking skills in Generation Z and the rise of plagiarism cases are a serious threat in the digital era. This study aims to analyze the integration of artificial intelligence utilization, examine the opportunities and challenges of artificial intelligence for Generation Z, and the impact of artificial intelligence on Generation Z in the digital era. This study uses a descriptive qualitative approach by examining various phenomena occurring in the current digital era. Data sources in this study refer to literature studies that refer to scientific journals, related books, and trusted internet sources. The results of this study indicate that the integration of artificial intelligence for Generation Z in the digital era must be accompanied by comprehensive knowledge and understanding so that Generation Z can utilize artificial intelligence wisely and responsibly. On the other hand, Artificial intelligence also provides considerable opportunities and challenges for Generation Z. Not only that, artificial intelligence also presents positive and negative impacts for Generation Z in the current digital era. The recommendation from this study is that a relevant strategy is needed to integrate artificial intelligence for Generation Z in the digital era. Also, the government, educational institutions, teachers, and the younger generation must collaborate in integrating artificial intelligence in the current digital era.